1997
DOI: 10.1021/jo971173i
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Partial Fluorination of Organic Compounds. 22.1 Highly Regioselective Anodic Monofluorination of Oxindole and 3-Oxo-1,2,3,4-tetrahydroisoquinoline Derivatives: Effects of Supporting Fluoride Salts and Anode Materials

Abstract: Highly regioselective monofluorination of 1-aryl-3-(phenylthio)oxindoles and 2-substituted-3-oxo-4-(phenylthio)-1,2,3,4-tetrahydroisoquinolines can be successfully carried out in the presence of Me4NF·4HF or Et4NF·3HF as a supporting electrolyte to provide the corresponding 3-fluorinated oxindole and 4-fluorinated isoquinoline derivatives in good yields. Carbon anodes as well as a platinum anode were found to be effective for the fluorination when Me4NF·4HF was used as the supporting electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Electrochemical fluorination of oxindole and cyclic phosphonate was achieved similarly. 46,47 It was also found that the selectivity of fluorination was strongly influenced by ionic liquid fluoride salts (Scheme 10). 48 Since Et 3 N-3HF contains the free base Et 3 N, the difluorinated product, once formed, was dehydrofluorinated to the monofluoro product.…”
Section: Selective Electrochemical Fluorination In Organic Solventsmentioning
confidence: 99%
“…Electrochemical fluorination of oxindole and cyclic phosphonate was achieved similarly. 46,47 It was also found that the selectivity of fluorination was strongly influenced by ionic liquid fluoride salts (Scheme 10). 48 Since Et 3 N-3HF contains the free base Et 3 N, the difluorinated product, once formed, was dehydrofluorinated to the monofluoro product.…”
Section: Selective Electrochemical Fluorination In Organic Solventsmentioning
confidence: 99%
“…Platinum has been typically employed for electrochemical fluorination as an anode material. However, carbon plate and carbon sheet anodes are also effective in the electrochemical fluorination of 1-phenyl-3-(phenylthio)­oxindole in Et 4 NF–4HF/MeCN, and a glassy carbon (GC) anode is much better than a Pt anode in some cases, as exemplified in Scheme . However, such anode material effects are case-by-case.…”
Section: Parameters For Selectivity and Efficiency In Electrochemical...mentioning
confidence: 99%
“…Highly regioselective, anodic monofluorination of oxindole and 3-oxo-1,2,3,4-tetrahydroisoquinoline can be achieved by using Et 4 NF-mHF (m = 3, 4) (Scheme 40) [67].…”
Section: Fluorination Of Heterocyclic Ringsmentioning
confidence: 99%